Development of Question-Based Exercise Books Minimum Competency Assessment for Students SMP - Erika Anugra Heni; Tri Novita Irawati; Sholahudin Al Ayubi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The background of this research is the need for AKM-based question practice books in implementing AKM in schools for junior high school students. This study aims to describe the process and results of developing a test book based on the Minimum Competency Assessment (AKM) for junior high school students. The type of research used is Research and Development (R&D) with the ADDIE model which consists of five stages, namely, 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The results of the AKM-based question practice book for junior high school students based on 2 material expert validators according to table 3.5 the classification of conversion of quantitative data to qualitative data, by validator 1 from the aspect of content eligibility and language eligibility aspects got a score of 3.86 and 3.69 in the